2010
DOI: 10.1007/s00436-010-2180-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of Echinostoma revolutum and Echinoparyphium recurvatum (Trematoda: Echinostomatidae) in Thailand and phylogenetic relationships with other isolates inferred by ITS1 sequence

Abstract: Echinostomatidae are common, widely distributed intestinal parasites causing significant disease in both animals and humans worldwide. In spite of their importance, the taxonomy of these echinostomes is still controversial. The taxonomic status of two species, Echinostoma revolutum and Echinoparyphium recurvatum, which commonly infect poultry and other birds, as well as human, is problematical. Previous phylogenetic analyses of Southeast Asian strains indicate that these species cluster as sister taxa. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Whereas the identifications based on comparisons with original species descriptions may be correct, failure to follow the subsequent taxonomic/systematic changes may results in 'discoveries' such as "Interestingly, this study revealed that E. revolutum was more closely aligned with E. recurvatum than the other species of genus Echinostoma (e.g., E. malayanum), contradicting traditional morphological taxonomy." (Saijuntha et al [63]) and "Interestingly, this study revealed that two species of genus Echinostoma, i.e. E. revolutum and E. malayanum do not cluster as a monophyletic clade and/or sister taxa."…”
Section: Asian Species Within the 'Revolutum' Groupmentioning
confidence: 77%
See 2 more Smart Citations
“…Whereas the identifications based on comparisons with original species descriptions may be correct, failure to follow the subsequent taxonomic/systematic changes may results in 'discoveries' such as "Interestingly, this study revealed that E. revolutum was more closely aligned with E. recurvatum than the other species of genus Echinostoma (e.g., E. malayanum), contradicting traditional morphological taxonomy." (Saijuntha et al [63]) and "Interestingly, this study revealed that two species of genus Echinostoma, i.e. E. revolutum and E. malayanum do not cluster as a monophyletic clade and/or sister taxa."…”
Section: Asian Species Within the 'Revolutum' Groupmentioning
confidence: 77%
“…Several notes of caution are required before considering the recent papers on "Echinostoma" spp. reported recently from Asian locations (Saijuntha et al [62][63][64]; Noikong et al [65]). First, the authors should be aware that annotations in GenBank solely reflect the identification (in most cases not supported by voucher material and/or morphological data) of the authors submitting the sequences.…”
Section: Asian Species Within the 'Revolutum' Groupmentioning
confidence: 94%
See 1 more Smart Citation
“…The use of molecular approaches to determine phylogenetic relationships of digeneans has grown very rapidly since 1990s and molecular-based studies on echinostomes have been carried out to date (Morgan and Blair 1995, 1998a, 1998b, 2000, Petrie et al 1996, Grabda-Kazubska et al 1998, Kostadinova et al 2003, Saijuntha et al 2011, Georgieva et al 2013, 2014, Noikong et al 2014, Selbach et al 2014, Kudlai et al 2015). The genus Echinochasmus Dietz, 1909 (as well as Echinostoma and Echinopharyphium ) is one of the most species–rich genera in Echinostomatidae (Kostadinova and Gibson 2000); however, no one species of this genus was involved in molecular phylogenetic studies of the Digenea (Cribb et al 2001, Olson et al 2003, Olson and Tkach 2005).…”
Section: Introductionmentioning
confidence: 99%
“…[42,43]. As a result, distinct species were molecularly identified, and genetic diversity within species has been estimated.…”
Section: Introductionmentioning
confidence: 99%